Disposable syringes for insulin injection. Issue 6176 (2nd June 1979) - Greenough, A; Cockcroft, P M; Bloom, A
Abstract : Results of a questionnaire on use of glass syringes among diabetic patients showed considerable variation in methods of keeping the syringes and in the duration of their useful life. Thirty patients took part in an investigation in which each patient used the same disposable syringe in place of the glass syringe for up to two months. No clinical or bacteriological evidence of infection was found. Used in this way, disposable syringes were less expensive than glass syringes. They are lighter than glass syringes, less susceptible to damage, and more easily carried on journeys.